2020
DOI: 10.4103/sjg.sjg_41_20
|View full text |Cite
|
Sign up to set email alerts
|

Risk of neutropenia in inflammatory bowel disease patients treated with TNF inhibitors: A single-center, retrospective cohort study

Abstract: Background/Aim: Tumor necrosis factor inhibitors (TNFi) have become the mainstay of treatment in moderate-to-severe cases of inflammatory bowel disease (IBD). Neutropenia has been reported in patients receiving TNFi for IBD and other diseases. In this study, we aimed to ascertain the relationship between the use of TNFi and the development of neutropenia in patients with IBD. Patients and Methods: This is a retrospective cohort study including all adult patients with IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Nevertheless, these are plausible predictors. Co-prescription of a thiopurine was a strong risk-factor for toxicity consistent with other studies 3840 . Abnormal blood-test results during the first six months of therapy were strong independent predictors of discontinuing 5-ASA with abnormal monitoring blood-test results, like previous reports about other drugs 23,41 .…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, these are plausible predictors. Co-prescription of a thiopurine was a strong risk-factor for toxicity consistent with other studies 3840 . Abnormal blood-test results during the first six months of therapy were strong independent predictors of discontinuing 5-ASA with abnormal monitoring blood-test results, like previous reports about other drugs 23,41 .…”
Section: Discussionsupporting
confidence: 89%
“…Anti-TNFs were evaluated in 10 studies 63–72 in patients with either RA, AS, PsO or PsA, 64 65 67 69 AS only, 66 2 in PsA only 68 72 and 3 in IBD. 63 70 71 Of the 10 studies, 1 used an RCT design, 68 1 a prospective cohort design 72 and the remaining were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…All 30 articles included in this systematic review were observational studies (seven cohort studies and 23 cross-sectional studies). Of the 30 studies, 26 (86.66%) obtained their data from an administrative database and/or patient interviewing [3,[14][15][16][17][18][21][22][23][24]26,[28][29][30][31][32][34][35][36][37][38][39][40][41], two studies (6.66%) from a survey [33,42], and two studies (6.66%) did not specify the data source [19,27]. Most of the studies reported the outcomes over a short period.…”
Section: Methodological Characteristics Of Included Studiesmentioning
confidence: 99%
“…All articles were written in English and conducted in Saudi Arabia. Thirteen studies were from the Riyadh region [3,[14][15][16][17][18][19][20][21][22][23][24][25], nine were from the Makkah region [26][27][28][29][30][31][32][33][34], three studies were from the Eastern region [35][36][37], three studies were from the Qassim region [38][39][40], one study was from the Najran region [41], and one study covered entire Saudi Arabia [42]. In relation to the range of years of publication, the oldest article was from 2012, and the latest was from 2021.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation